南极产低温蛋白酶菌株Marinobacter sp.R2的发酵条件及酶学性质研究 - 林念炜; 张锐; 赵晶; 曾润颖 (2004)
从南极海域沉积物中筛选到一产蛋白酶的菌株R2,经细菌学形态特征鉴定及16SrDNA序列分析鉴定,该菌株属于海杆菌属(Marinobacter).生长特性研究表明该菌株属于兼性嗜冷菌,其最适生长温度为10～15℃.R2菌株能利用多种碳源产酶,最适产酶温度为20℃.粗酶液经硫酸铵盐析、DEAEcellulose 52柱层析进行初步分离纯化后进行酶学性质的研究.该菌株所分泌蛋白酶的最适作用温度为20℃,最适pH值为9～10,对热敏感,是典型的低温碱性蛋白酶.Ca2+、Mn2+、Cu2+对该蛋白酶有较为明显的激活作用,而Cd2+、Co2+则能抑制酶活.高浓度的变性剂、PMSF、AEBSF和EDTA都能抑制该蛋白酶,表明该酶属于丝氨酸蛋白酶,且金属离子对酶活性中心构象有关键性的影响. A strain R2,which produces protease,was isolated from the Antarctic Ocean sediment samples.Results of morphology and 16S rDNA sequence analysis showed that R2 belonged to Marinobacter.The Marinobacter sp.strain R2 was facultative psychrophile because it grew best at 10～15℃.The strain could produce protease with many kinds of single carbonaceous substance,and produced maximum protease activity at 20℃.The primary purification was performed by ammonium sulfate fractionation and column chromatography with DEAE cellulose-52.The optimum condition for the protease activity was 20℃ and pH 9～10,which suggested the enzyme was a typical alkaline cold-active protease.The protease activity was stimulated by Ca~(2+)、Mn~(2+)、Cu~(2+),and was inhibited by Cd~(2+)、Co~(2+).This enzyme appeared to be a serine protease,on the basis of its sensitivity to PMSF and AEBSF.From the result that EDTA showed obvious inhibiting effect on the enzyme,it can be suggested that metal ions played an important role in the conservation of enzyme conformation for the catalytic activity. 国家海洋局青年基金(98310);; 国家海洋局项目(科01303)资助